(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2025)
The aim of the study was to determine the effectiveness of growth regulators in increasing seed productivity of tomato under open-field conditions of the Left-Bank Forest-Steppe of Ukraine. Field experiments were conducted at the Institute of Vegetable and Melon Growing of the National Academy of Agrarian Sciences of Ukraine using the preparations Aminoplacentin, Lipoplacentin, and Cryoplacentin (protein–peptide complexes isolated from the placenta of farm animals through cryocavitation and cryoconcentration; Institute for Problems of Cryobiology and Cryomedicine of the National Academy of Sciences of Ukraine), PEO (a cryoprotectant), and a suspension culture of the microalga Coelastrella thermophila var. globulina grown in BG-11 medium. It was established that seed treatment with stimulatory preparations (Aminoplacentin, Lipoplacentin, Cryoplacentin, PEO-1000, and Coelastrella thermophila var. globulina extract) significantly increased tomato plant height by 9.7–15.9%, the number of leaves on the main stem by 8.6–12.2%, the number of first-order shoots by 16.6–28.5%, and the number of inflorescences on the main stem by 15.7–22.0%. The greatest positive effect on these biometric parameters was observed with Aminoplacentin, Lipoplacentin, Cryoplacentin, and PEO-1000, which also increased tomato seed yield by 4.22–18.28 kg/ha, or 9.84–42.61%, relative to the control yield of 42.9 kg/ha. The highest seed yield was obtained with the cryoprotective preparation PEO-1000 (61.18 kg/ha). A trend toward increased germination energy was recorded when using Aminoplacentin, Lipoplacentin, Cryoplacentin, and PEO-1000 (95.8–96.6%), along with improved laboratory germination across all tested preparations (98.0–98.5%).